A practical iodine-catalyzed oxidative conversion of aldehydes to nitriles. Issue 3 (5th January 2017) - Fang, Chaojie; Li, Meichao; Hu, Xinquan; Mo, Weimin; Hu, Baoxiang; Sun, Nan; Jin, Liqun; Shen, Zhenlu
Abstract : A simple and efficient method for the direct synthesis of nitriles from aldehydes using ammonium acetate as the nitrogen source, iodine as the catalyst, and tert -butyl hydroperoxide (TBHP) as the oxidant was developed. Abstract : A simple and efficient method for the direct synthesis of nitriles from aldehydes using ammonium acetate as the nitrogen source has been developed. The reactions were performed with iodine as the catalyst and tert -butyl hydroperoxide (TBHP) as the oxidant under mild conditions. A variety of aromatic, heteroaromatic, aliphatic and allylic aldehydes could be converted into their corresponding nitriles in good to excellent yields.